Transferências voluntárias e corrupção municipal no Ceará: evidências preliminares dos registros de contas irregulares do TCE - Oliveira, Liliana Costa de (2019)
This research investigates whether there is a correlation between the number of cases judged irregular by the Court of Audit of the State of Ceará in the municipalities of Ceará and political and electoral variables. For this, a negative binomial regression model is estimated for panel data from the 184 municipalities of Ceará between 2007 and 2016. The results indicate a low positive correlation between number of irregularities and current voluntary transfers from the State to the municipalities. In the years of municipal elections and for the State Government there is a reduction of -67.46% and -55.66% in the expected number of irregularities, respectively.